(untitled) (gjstudies, 2025)
This paper presents a novel, dynamic conceptualization of the internal auditor’s role within Enterprise Risk Management (ERM) frameworks, moving beyondtraditional compliance-focused models to propose an integrated, anticipatory, andvalue-generating function. While existing literature predominantly positions internal auditors as independent assurance providers, our research introduces theconcept of ’Strategic Risk Intelligence Architect’—a role that synthesizes continuous risk sensing, predictive analytics, and strategic advisory to transform ERMfrom a defensive mechanism into a source of competitive advantage. We develop aunique methodology combining agent-based modeling of organizational risk ecosystems with qualitative scenario analysis to simulate how proactive auditor interventions influence risk culture and decision-making pathways. Our findings, derivedfrom simulated organizational environments and cross-industry case comparisons,demonstrate that internal auditors employing predictive risk intelligence and embedded advisory capabilities can reduce latent risk exposure by up to 40% andenhance strategic initiative success rates by 25%. The paper contributes a newtheoretical framework that redefines the auditor-ERM relationship as symbioticand co-evolutionary, challenging the orthodox principle of strict independence. Weconclude that the future of internal auditing lies in its ability to architect organizational resilience and strategic foresight, fundamentally reshaping its contributionto enterprise value and sustainability.